Augmented [videorecording (DVD)] - Gil, Gideon; MacDonald, Heather (Heather Lyn); Orr, Matthew (Motion picture director); Herr, Hugh (PBS, 2022)
In Augmented, Hugh Herr, a biophysicist working to create brain-controlled robotic limbs, shares his personal journey. At age 17, Herr's legs were amputated after a climbing accident. Frustrated by the crude prosthetic limbs he was given, Herr set out to remedy their design, leading him to a career as an inventor of innovative prosthetic devices. Now, Herr is teaming up with an injured climber and a surgeon at a leading Boston hospital to test a new approach to surgical amputation that allows prosthetic limbs to move and feel like the real thing. Herr's journey is a powerful tale of innovation and the inspiring story of a personal tragedy transformed into a life-long quest to help others.